Technologies de l’information et de la communication et diffusion du français : usages, représentations, politiques - Jeannine Gerbault (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Data was collected in a survey conducted in Francophone cultural institutions worldwide in order to understand how ICT (Information and Communication Technology) modifies the ways in which the French language and culture are accessed, taught, and learned. A number of processes were identified in the behaviors and attitudes observed in actual and potential users of ICT. To explain how the changes triggered by the development of ICT are integrated into scenarios of contact with the French language, the data is analyzed as representing stages in the adoption of innovation, stages which may be dependent on contextual variables. The relationship between official and actual language policy concerning French as a foreign language is presented. A model of development of the adoption of ICT is suggested, in which the various responses to the penetration of ICT are presented as a coherent set of stages. Finally, guidelines for the effective dissemination of French in the context of ICT are outlined.